Performance evaluation of DPS coordination strategies modelled in pi-calculus. (17th December 2009) - Khorasani, Elham S.; Carver, Norman; Rahimi, Shahram
Distributed problem solving (DPS) is the subfield of multi-agent systems concerned with using systems of agents to solve large-scale, distributed problems like data interpretation in sensor networks. Coordination of agent actions is a key issue in DPS. There are not yet methods that can automatically produce effective coordination strategies for most real-world applications. We envision a tool that would support human engineering by allowing a strategy to be modelled at various levels of abstraction, with incomplete specification of the inter- and intra-agent order of actions. The tool would be able to analyse various properties of such strategies, determine the best possible time performance, and derive ordering constraints to guarantee best performance. This paper reports on research to develop key elements for such a tool, including using pi-calculus as a formal framework for defining DPS coordination strategies, and techniques for evaluating the time performance of such strategies defined with pi-calculus.